Kewenangan MPD Pasca Putusan MK Nomor 49/PUU-X/2012 Dikaitkan Dengan Hak Ingkar Notaris - Yolanda, Oppie; Pujiono, Pujiono (Notarius, 2023)
AbstractThe Supreme Court Decision No. 49/PUU-X/2012 has invalidated article 66 paragraph (1) of Law No. 30 of 2004 concerning the Notary Office regarding the authority of the Regional Supervisory Assembly in terms of granting approval regarding the presence of notaries in a legal process requested by law enforcement to the need for the minuta deed and/or notary protocol which is part of the notary's duty to maintain the confidentiality of its clients. The methods carried out in this study are normative juridical. The results of the discussion in this study are the authority of the MPD after the decision of MK No. 49 / PUU-X / 2012 limited to article 70 UUJN and changes in the regulation of the Notary Office after the Decision of MK No. 49 / PUU-X / 2012 which abolished the authority of the MPD in giving approval, has been replaced by the MKN contained in Article 66 paragraph (1) of the PUUJN.keyword: notary; constitutional court; denial rightsAbstrakPutusan Mahkamah Agung No, 49/PUU-X/2012 telah membatalkan bunyi Pasal 66 ayat (1) Undang-Undang No. 30 Tahun 2004 perihal Jabatan Notaris mengenai kewenangan Majelis Pengawas Daerah dalam hal pemberian persetujuan terkait kehadiran notaris dalam suatu proses hukum yang diminta oleh penegak hukum hingga kebutuhan atas minuta akta maupun protokol notaris yang mana perihal itu merupakan bagian dari tugas notaris untuk menjaga kerahasiaan kliennya. Prosedur pada kajian ini, yaitu yuridis normatif. Hasil pembahasan pada kajian ini ialah kewenangan MPD pasca putusan MK Nomor 49/PUU-X/2012 terbatas pada Pasal 70 UUJN serta Perubahan aturan Jabatan Notaris sesudah Putusan MK Nomor 49/PUU-X/2012 melakukan penghapusan wewenang MPD dengan menyetujui sudah tergantikan oleh MKN yang termuat di Pasal  66  ayat (1)  PUUJN.Kata kunci: notaris; mahkamah konstitusi; hak ingkar